Market Orientations Analysis in Industrial Factories: A Case Study in Iraqi School Supplies Factory - Mudher Salih Mahdi; Sarmad Hamza Jassim; Ahmad Falih Ahmad (Penerbit Jurnal Indonesia, 2026)
Aresearch aims to enhance factory's sales through good planning and implementation of types of market orientations, which are product orientation, salling orientation, marketing orientation, and community orientation. Research was conducted in Iraqi School Supplies Factory with direct interviews of (27) managers, whose average opinions were recorded in examination form that was prepared specifically to measure reality of four variables investigated. It reveals gaps in factory's focus on four types of market orientations. Research recommends that factories that do not have professional marketing staff should use services of specialized marketing agencies in order to ensure that factory achieves required balance in market orientations.